Content-specific activational effects of estrogen on working memory performance - Vranić, Andrea (Array, 2008)
This study aimed at exploring the influence of the task content and the menstrual cycle phase on working memory (WM) performance. The content-specificity of WM was addressed within the framework of evolutionary psychology, proposing a hormone-mediated adaptive design governing face perception. Two groups of healthy young women (n=66 regular menstrual cycle, and n=27 on oral contraceptives users) were tested on a WM task with adult male or infant face photographs. ANOVA showed significant interaction between task content and estrogen level: women were more efficient in solving the male faces task during high- compared to low-estrogen phase of the cycle. No differences were found in the efficacy of solving the infant faces task between different phases of the cycle. Results suggest content-specific activational effects of estrogen on the WM performance and are consistent with the notion of a hormonal mechanism underlying adaptive shifts in cognition related to the mating motivation.